Kemunculan penyakit berjangkit dan kesannya terhadap manusia di Malaysia - Fatan Hamamah Hj. Yahaya (Universiti Kebangsaan Malaysia, 2005)
Contagious diseases are biosocial phenomena that can appear anywhere and at any time. They are caused by infectious or toxic agents that are dangerous to human beings, and therefore carry certain social, economic and political implications. If allowed to spread, they constitute a real danger to society and the nation. I shall discuss several contagious diseases common to Malaysia, and highlight their causes and the possible methods of prevention. The battle against them is never easy